La haine à l’œuvre dans Carpenter’s Gothic (1999) de William Gaddis - Jacques Sohier (Revue LISA)
In Carpenter’s Gothic hatred is given pride of place. William Gaddis delineates a society in which hatred proliferates. Characters are caught in the turmoils of their hatred whether it derives from the Vietnam War or from fundamentalist movements, from their individualistic quest for social recognition or from self-aggrandizement. We mean to develop a typology derived from psychoanalysis or anthropology so as to take into account all the different facets hate has in the novel. We shall devote analyses to jealousy caused by hatred, then describe the primary hate that underpins all types of relationships as a preliminary study to questioning the excess that fuels Gaddis’s writing. Lastly, by referring to the author’s non-fictional work we shall put forward the thesis that the voluble protagonist is to a large extent the author’s mouthpiece. McCandless’s vindictive disquisitions on the course of the world will be seen as the equivalent of a tragic mask through which William Gaddis gives vent to his melancholia and intense detestation of the ways of the world.